2007
DOI: 10.1210/jc.2007-0718
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Deficiency Increases the Risk of Preeclampsia

Abstract: Maternal vitamin D deficiency may be an independent risk factor for preeclampsia. Vitamin D supplementation in early pregnancy should be explored for preventing preeclampsia and promoting neonatal well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
586
10
50

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 784 publications
(688 citation statements)
references
References 44 publications
25
586
10
50
Order By: Relevance
“…This study reported a decrease in the inflammatory response with vitamin D treatment by measurement of IL-8 [24]. Also of note, vitamin D has been associated with increased risk of preeclampsia [25], infants that are small for gestational age (SGA) [26][27][28][29], cesarean section [30], and gestational diabetes (GDM) [31].…”
Section: Pregnancy Lossmentioning
confidence: 73%
“…This study reported a decrease in the inflammatory response with vitamin D treatment by measurement of IL-8 [24]. Also of note, vitamin D has been associated with increased risk of preeclampsia [25], infants that are small for gestational age (SGA) [26][27][28][29], cesarean section [30], and gestational diabetes (GDM) [31].…”
Section: Pregnancy Lossmentioning
confidence: 73%
“…4,5). Placental expression of inflammatory cytokines is part of normal immune function during pregnancy (32), but overexuberant cytokine responses are also known to play a key role in adverse outcomes of pregnancy (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the latter, impaired vitamin D status during gestation is associated with poor skeletal growth in childhood (3), consistent with the classical functions of vitamin D. However, low maternal levels of the major circulating form of vitamin D, 25-hydroxyvitamin D 3 (25OHD 3 ), have also been linked to adverse outcomes in pregnancy such as pre-eclampsia, a disorder involving dysregulated placental vascularization that affects up to 10% of pregnancies (5,6). In this way, the physiological impact of maternal vitamin D status may not be restricted to the endocrine regulation of skeletal homeostasis, but may also extend to more localized events in the placenta.…”
mentioning
confidence: 99%
“…An NCCS found that a 50-nmol/l decline in 25(OH)D concentration doubled the risk of pre-eclampsia (adjusted odds ratio 2.4; 95% confidence interval 1.1-5.4) (Bodnar et al, 2007). In a study in South Carolina, subjects with early-onset severe pre-eclampsia (n ¼ 50) had lower total 25(OH)D levels than those of healthy control subjects (n ¼ 100; Po0.001).…”
Section: Maternal Sepsismentioning
confidence: 99%